Nutritional Importance of Three Potamidid Snails from Bhavanapadu Mangrove Creek: Lipid Profiling by GC-MS: A Relative Exploration - Ranjan, T. Joseph Uday; Babu, K. Ramesh (Pakistan Journal of Nutrition, 2016)
Background: Seafood is one of the most nutritionally balanced foods. Studies on fatty acid composition of commercial seafood in India are limited. This might be due to lack of awareness on the benefits of these nutrients particularly from molluscan meat. Objective: The present comparative study aims on providing qualitatively the fatty acid composition in total tissue of three potamidid snails specifically Telescopium telescopium , Cerithidea obtusa and Cerithidea cingulata of Tekkali Creek, Srikakulam district, Andhra Pradesh. Methodology: The total fatty acid compositional studies were performed by using FAME and GC-MS analysis. Results: The results showed that Telescopium telescopium was a complex mixture of numerous compounds, among them, palmitic acid (C16:0), lauric acid (C12:0), myristic acid (C14:0) and oleic acid (18:1) appears to be the significant ones along with essential fatty acid γ-linolenic acid (C18:3 n-6). Cerithidea obtusa was amalgamated mixture of copious compounds, among them essential fatty acid methyl linoleate (C19:2 n-6), margaric acid methyl ester (C18:0), 11-hexadecenoic acid methyl ester (C17:1) and 1-eicosanol (C20:0) were distinctive fatty acids, oleic acid (18:1) and palmitic acid (C16:0) appears to be the noteworthy one along with essential fatty acid γ-linoleic acid (C18:3 n-6). Cerithidea cingulata was a complex combination of mix, among them tridecanoic acid methyl ester (C14:0), palmitoleic acid methyl ester (C17:1) and 1-pentadecane (C15:0) were unique fatty acids, palmitic acid (C16:0) appears to be the striking one along with essential fatty acid γ-linolenic acid (C18:3 n-6). Conclusion: These findings concluded that these can be utilized as potential fishery resource for nutrition, particularly in developing countries by being constituents in food to prevent malnutrition.